AKUISISI DATA UNTUK PERCOBAAN FISIKA BERBASIS ARDUINO UNO DI SMKN 1 GAMBUT - Rizali, Muhammad; Uli, Agustina Hotma; Siska, Madschen Sia Mei Ol; Wusko, Ikna Urwatul (Politeknik Negeri Banjarmasin, 2020)
Lacks of facility and equipments in physics/science experiment is the problem in school activity, due to prising and availability of the equipment. The lack of facility and equipment can cause lower quality of student education. Solutions needed to solve this problem. In this community service, Arduino Uno with sensor physics and data acquisition experiment equipment introduced. Introduction about input-output pin in Arduino, temperature sessor LM35, coding language, and air temperature data acquisition, explained to student and teacher. The results are the experiment well done, learning that interests students to participate actively, additional knowledge for the teacher, and the higher motivation of students and teachers to study further.